Gaming Disorder: News Media Framing of Video Game Addiction as a Mental Illness. Issue 5 (1st December 2020) - Parrott, Scott; Rogers, Ryan; Towery, Nathan A.; Hakim, Samuel D.
ABSTRACT: In May 2019, the World Health Organization identified "gaming disorder" as a mental illness. The decision followed debate in which the video game industry, gamers, and researchers disagreed over whether sufficient research existed to identify gaming disorder as a mental illness. Informed by framing theory, the present study examined news coverage of the decision in the year leading to and immediately following the controversial classification. The study determined how journalists framed gaming disorder in terms of (a) defining the problem, (b) identifying causes, (c) advancing treatment recommendations, and (d) extending moral evaluations. Results suggest that journalists arguably legitimized the illness classification.